Implementation and operational feasibility of SAMBA I HIV‐1 semi‐quantitative viral load testing at the point‐of‐care in rural settings in Malawi and Uganda. Issue 2 (3rd December 2020) - Gueguen, Monique; Nicholas, Sarala; Poulet, Elisabeth; Schramm, Birgit; Szumilin, Elisabeth; Wolters, Liselotte; Wapling, Johanna; Ajule, Ephrahim; Rakesh, Ankur; Mwenda, Reuben; Kiyaga, Charles; Balkan, Suna
Abstract: Objective: We monitored a large‐scale implementation of the Simple Amplification‐Based Assay semi‐quantitative viral load test for HIV‐1 version I (SAMBA I Viral Load = SAMBA I VL) within Médecins Sans Frontières' HIV programmes in Malawi and Uganda, to assess its performance and operational feasibility. Methods: Descriptive analysis of routine programme data between August 2013 and December 2016. The dataset included samples collected for VL monitoring and tested using SAMBA I VL in five HIV clinics in Malawi (four peripheral health centres and one district hospital), and one HIV clinic in a regional referral hospital in Uganda. SAMBA I VL was used for VL testing in patients who had been receiving ART for between 6 months and ten years, to determine whether plasma VL was above or below 1000 copies/mL of HIV‐1, reflecting ART failure or efficacy. Randomly selected samples were quantified with commercial VL assays. SAMBA I instruments and test performance, site throughput, and delays in communicating results to clinicians and patients were monitored. Results: Between August 2013 and December 2016 a total of 60 889 patient samples were analysed with SAMBA I VL. Overall, 0.23% of initial SAMBA I VL results were invalid; this was reduced to 0.04% after repeating the test once. Global test failure, including instrument failure, was 1.34%. Concordance with reference quantitative testing of VL was 2620/2727, 96.0% (1338/1382, 96.8% in Malawi; 1282/1345, 95.3% in Uganda). For Chiradzulu peripheral health centres and Arua Hospital HIV clinic, where testing was performed on‐site, same‐day results were communicated to clinicians for between 91% and 97% of samples. Same‐day clinical review was obtained for 84.7% across the whole set of samples tested. Conclusions: SAMBA I VL testing is feasible for monitoring cohorts of 1000 to 5000 ART‐experienced patients. Same‐day results can be used to inform rapid clinical decision‐making at rural and remote health facilities, potentially reducing time available for development of resistance and conceivably helping to reduce morbidity and mortality. Abstract : Objectif: Nous avons suivi une mise en œuvre à grande échelle du test de la charge virale semi‐quantitative du VIH ‐1 basé sur de Test de Simple Amplification version I (SAMBA I Viral Load = SAMBA I VL) au sein des programmes VIH de Médecins Sans Frontières au Malawi et en Ouganda, afin d'évaluer sa performance et sa faisabilité opérationnelle. Méthodes: Analyse descriptive des données du programme de routine entre août 2013 et décembre 2016. L'ensemble des données comprenait des échantillons collectés pour le suivi de la CV et testés à l'aide de SAMBA I VL dans cinq cliniques VIH au Malawi (quatre centres de santé périphériques et un hôpital de district), et une clinique VIH dans un hôpital régional de référence en Ouganda. SAMBA I VL a été utilisé pour le test de la CV chez les patients qui recevaient l'ART depuis 6 mois à dix ans, afin de déterminer si la CV plasmatique était supérieure ou inférieure à 1000 copies/ml de VIH‐1, reflétant l'échec ou l'efficacité de l'ART. Des échantillons sélectionnés aléatoirement ont été quantifiés avec des tests de CV commerciaux. Les instruments de SAMBA I et les performances des tests, le débit du site et les délais dans la communication des résultats aux cliniciens et aux patients ont été suivis. Résultats: Entre août 2013 et décembre 2016, un total de 60.889 échantillons de patients ont été analysés avec SAMBA I VL. Dans l'ensemble, 0, 23% des résultats initiaux de SAMBA I VL étaient invalides; ceux‐ci ont été été réduits à 0, 04% après avoir répété le test une fois. L'échec global du test, y compris l'échec de l'instrument, était de 1, 34%. La concordance avec les tests quantitatifs de référence de la CV était de 2620/2727; 96, 0% (1338/1382; 96, 8% au Malawi; 1282/1345; 95, 3% en Ouganda). Pour les centres de santé périphériques de Chiradzulu et la clinique VIH de l'hôpital d'Arua, où les tests ont été effectués sur place, les résultats ont été communiqués le jour même aux cliniciens pour entre 91% et 97% des échantillons. Un examen clinique le jour même a été obtenu pour 84, 7% de l'ensemble des échantillons testés. Conclusions: Le test SAMBA I VL est réalisable pour le suivi de cohortes de 1.000 à 5.000 patients déjà sous ART. Les résultats le jour même peuvent être utilisés pour éclairer la prise de décision clinique rapide dans les établissements de santé ruraux et éloignés, réduisant potentiellement le temps disponible pour le développement de la résistance et contribuant éventuellement à réduire la morbidité et la mortalité.